1986
DOI: 10.3109/02656738609016488
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia, chemotherapeutic agents and oncogenic transformation

Abstract: The modulating effects of hyperthermia on cytotoxity and oncogenicity of several chemotherapeutic agents were investigated using the C3H 10T1/2 cell system. Logarithmic phase cultures of 10T1/2 cells were treated with various doses of cis-platinum or bleomycin sulphate for 2 h, either alone or with simultaneous hyperthermia (42 degrees C for 2 h). In a second set of experiments, cells were treated for 24 h with either melphalan or cis-platinum followed by a 2 h heat treatment. While hyperthermia alone was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In previous studies, tolerable hyperthermia alone was reported to be insufficient for complete suppression of tumors,27,31 so combination therapy with hyperthermia is necessary for complete tumor suppression. We are continuing our search for suitable drugs to use concomitantly with inductive hyperthermia and ferucarbotran to enhance the antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, tolerable hyperthermia alone was reported to be insufficient for complete suppression of tumors,27,31 so combination therapy with hyperthermia is necessary for complete tumor suppression. We are continuing our search for suitable drugs to use concomitantly with inductive hyperthermia and ferucarbotran to enhance the antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…This combination of treatment was ineffective on the primary tumour, but rapid and massive metastases developed in distant organs including the lung. Furthermore, the chemo-drugs Bleomycin and Cisplatin have been found to turn carcinogenic in vitro by heat-therapy [25] [26] [27].…”
Section: Systemic or Loco-regional Heating?mentioning
confidence: 99%
“…14 Hyperthermia has been used for many years to treat a wide variety of tumors in both experimental animals and patients. 15,16 The therapeutic effects of hyperthermia are mainly attributed to the heat-induced tumor cytotoxicity, 16,17 alteration of tumor metabolism, 18,19 enhanced blood flow and increased tumor sensitivity to combined chemotherapy or radiotherapy. [20][21][22] It is also reported that hyperthermia can induce cellular damage, necrosis or apoptosis, directly.…”
mentioning
confidence: 99%
“…Intratumoral injection of autologous DC or combination of hyperthermia with other approaches has been demonstrated to be efficient in tumor immunotherapy. 1,[15][16][17] We hypothesize that combination of local hyperthermia (LHT) with intratumoral injection of DC will synergize the benefits of hyperthermia-induced tumor cell apoptosis and HSPs release with DC-mediated tumor antigen uptake and presentation. [27][28][29][30][31][32][33][34][35][36][37] In this study, we evaluated the safety and efficiency of the combined therapy in 9 patients with metastatic melanoma (n 5 9), and compared them with intratumoral injection of immature DC (IT-DC) alone in 9 patients.…”
mentioning
confidence: 99%